MARKETPLACE RESPONSIBILITY IN INDONESIA FOR THE RISE OF INTELLECTUAL PROPERTY RIGHTS VIOLATIONS: REGULATORY REVIEW AND PREVENTION EFFORTS - Anissa Aulia Murdijanto; Devika Tryza Ayodhya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The study provides an in-depth examination of the legal responsibilities borne by marketplace platforms in Indonesia amidst the growing incidence of Intellectual Property Rights (IPR) violations, particularly the circulation of counterfeit goods and illegal content in digital spaces. This research focuses on analyzing key regulatory frameworks, including the Copyright Law, Trademark and Geographical Indication Law, the Government Regulation on Electronic Commerce, and additional policies from the Ministry of Communication and Informatics that collectively govern marketplace obligations regarding supervision, content moderation, and legal liability for non-compliance. Employing a normative legal research approach, the study investigates the legal grounds that establish reporting mechanisms for infringements as well as the possibilities for civil and criminal remedies available to brand or rights holders. Beyond enforcement, this research also highlights the importance of preventive strategies, such as seller verification systems, the use of automated detection technologies, user education, and inter-institutional collaboration. The findings indicate that marketplaces that consistently implement legal enforcement systems and comprehensive preventive measures can foster a healthier digital economic ecosystem while simultaneously strengthening the protection of creators’ rights and consumer safety.